A Case of Complete Recovery From Recurrent Bell’s Palsy After Peripheral Blood Stem Cell Transplantation : A Case of Complete Recovery From Recurrent Bell’s Palsy After Peripheral Blood Stem Cell Transplantation - lim, hadyanto; Hutasoit, Eka Samuel P; Endy Juli Anto (Universitas Methodist Indonesia, 2024)
Background Recurrent Bell’s palsy is a rare condition that can affect the ipsilateral or contralateral to the affected side of the primary attack. There is still no consensus on treatment guidelines for recurrent Bell’s palsy. Therefore, we report a case of idiopathic recurrent contralateral facial palsy treated with autologous peripheral blood stem cell (PBSC) transplantation. Case Presentation A 72-year-old man presented with the sudden onset of right facial weakness, which was contralateral to the affected side of the first episode of facial palsy. The weakness had progressed with difficulty in closing the right eye, drooling the water from the right side of the mouth, and chewing impairment which was consistent with House Brackmann grade IV or moderately severe facial nerve grading system. He had exposure to cold stimulation, and a history of hypertension. He was given G-CSF 10 ug/kg/day for 5 days to mobilize stem cells, followed by apheresis on the 5th day. He did not receive acupuncture treatment. He had a complete recovery in 3 weeks with House Brackmann grade I or normal function of facial nerve. Conclusion Peripheral blood stem cell transplantation had a beneficial effect on the complete recovery of this recurrent Bell’s palsy and provides a treatment strategy in patients with unilateral facial palsy.